Persepsi Mahasiswa Manajemen Bisnis Terhadap Auditor: Pengaruh Kedekatan dan Pengetahuan Terhadap Stereotip Auditor - Sri Andayani; Rizki Lanniari HS (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the factors that affect the perception of business management students at the Batam State Polytechnic towards the auditor profession, focusing on their views on the career, employment, and image of auditors. Through a replication approach from previous studies, this study takes steps to understand how these factors play a role in shaping student perceptions. This study uses a quantitative approach, with the research population including 652 Business Management students at the Batam State Polytechnic who are enrolled in the Managerial Accounting and Accounting study program in the 3rd and 4th years of the 2023/2024 academic year. Using the Slovin formula model, the number of selected samples was 87 people. The results of the analysis showed that several factors such as knowledge, media, academic training, satisfaction with auditing courses, and experience in participating in auditing seminars/courses, had a significant effect on students' perception of the auditor profession. However, having auditor acquaintances and having family/friends as sources of information related to the auditor profession, has not been proven to have a significant influence on student perception.